Analisis bibliometrik dari penelitian desain didaktis di sekolah dasar - Sari, Indah Puspita; Supriyadi, Edi; Suryadi, Didi (IKIP Siliwangi, 2023)
By using bibliometric analysis with Biblioshiny and computational mapping with VOSviewer, the purpose of this investigation is to investigate the evolution of research on didactic design in primary schools. In order to obtain data from the Dimension software, which served as a reference manager, we searched the titles and abstracts of papers for the terms